2015
DOI: 10.3389/fmicb.2015.01331
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Amino Acid Auxotrophy in Bifidobacterium bifidum PRL2010

Abstract: The acquisition and assimilation strategies followed by members of the infant gut microbiota to retrieve nitrogen from the gut lumen are still largely unknown. In particular, no information on these metabolic processes is available regarding bifidobacteria, which are among the first microbial colonizers of the human intestine. Here, evaluation of amino acid auxotrophy and prototrophy of Bifidobacterium bifidum, with particular emphasis on B. bifidum strain PRL2010 (LMG S-28692), revealed a putative auxotrophy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 45 publications
3
56
0
Order By: Relevance
“…We observed that the model did not demonstrate growth on fructose as the sole carbon source; to address these, we added additional transport reactions for fructose and glucose, expanding the model. Finally, our simulations were consistent with reported experiments, confirming the accuracy of the model in utilising different carbon sources 42 .…”
Section: Model Expansion To Account For Experimental Growth Profilessupporting
confidence: 88%
“…We observed that the model did not demonstrate growth on fructose as the sole carbon source; to address these, we added additional transport reactions for fructose and glucose, expanding the model. Finally, our simulations were consistent with reported experiments, confirming the accuracy of the model in utilising different carbon sources 42 .…”
Section: Model Expansion To Account For Experimental Growth Profilessupporting
confidence: 88%
“…The luminal microbiomes of functional cluster 1 had a higher abundance (69-fold) of Bifidobacterium than those in functional cluster 2, while those of functional cluster 2 had a higher abundance of sulfur-reducing bacteria (SRB) than functional cluster 1. A recent study has shown that Bifidobacterium utilizes milk protein effectively and requires cysteine, a sulfide amino acid, for growth (37). SRB also utilize cysteine as an energy source (38).…”
Section: Discussionmentioning
confidence: 99%
“…In the LFH‐GOS conjugates sample, at the end of digestion, the protein fraction was mainly composed of (conjugated) peptides, whereas the protein fraction in the unconjugated components sample underwent complete proteolysis and was composed of mainly amino acids, in accordance with the results of Wang et al for pure LF. Peptides are the preferred substrates for many colonic bacteria because of kinetic advantages of peptide‐uptake systems in comparison with those for free amino acids, partially explaining the superior growth rate of L. casei on the conjugates. A more exciting possible explanation is that transporters on the cell surface of lactobacilli, which are involved in GOS uptake, had bound the GOS fraction and started its uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, probiotic bacteria are auxotrophic for some amino acids and require their presence to grow. 9,10 For example, leucine, phenylalanine, glutamic acid, valine, cysteine, tryptophan, and tyrosine are essential for the growth of Lactobacillus casei, 11,12 and certain bifidobacteria require cysteine. 10,13 Here, we propose the next generation of prebiotics: proteincontaining prebiotics.…”
mentioning
confidence: 99%
See 1 more Smart Citation